Galona's review of victim labelling theory: A rejoinder - Van Dijk, Jan (International review of victimology, 2019)
In this article the author responds to a review by Galona (2018) of the historical-theological parts of victim labelling theory as elaborated previously in this journal and elsewhere (van Dijk, 2009). According to Galona, the term ‘victima/victim' as a special name for Jesus Christ was not coined by Reformation theologians like Calvin, as asserted by van Dijk, but was for example already widely used by Roman poets. It also appeared in pre-Reformation theological writings for centuries. In his rejoinder, the author explains that Roman poets indeed sometimes used the term ‘victima' for human beings but did so in a purely metaphorical sense. He agrees with Galona that the use of this label in its figural sense denoting Christ's deep and innocent suffering emerged in theological writings pre-dating the Reformation. However, the label only ‘went viral' around the time of the Reformation and has, from that time onwards, been the universal colloquial term for ordinary people victimised by crime across the Western world. In the second part of the article, the author elaborates on the theoretical and practical implications of the Christian roots of the ‘victima' label. For centuries, victims of crime were expected to undergo their suffering meekly, in imitation of Christ. Ongoing secularisation has emancipated crime victims from the restraining ‘victima' label, allowing them to freely speak up for themselves. Recent victim-friendly reforms of criminal justice have been driven by the need to find a new, victim-centred legitimacy in an increasingly secularised world.